EFFECT OF FERMENTED CACAO POD SUPPLEMENTATION ON SHEEP RUMEN MICROBIAL FERMENTATION - Wulandari, S.; Agus, A.; Cahyanto, M. N.; Utomo, R. (Journal of the Indonesian Tropical Animal Agriculture, 2014)
The objective of this research was to improve beneficial value of cacao pod as sheep feedingredients comprising up to 50% total feed. This research was conducted in two stages. Stage 1 wascacao pod fermentation. Completely randomized design with 3x3 factorial patterns was used in thisstage, in which factor I was microbial inoculum dosage of 0%, 0.05% and 0.1% and factor II wasincubation period of 0, 3 and 6 days. Result demonstrated that six-day fermentation with 0.05%microbial inoculum could lower cacao NDF, ADF and theobromine. The optimum inoculum dosage andfermentation time from stage 1 was applied to stage 2. Stage 2 was rumen microbial fermentation test.This research administrated 3x3 of latin square design. In period I sheep were fed with CF0 (nonfermentedcomplete feed), in period II sheep were given CF 1 (complete feed containing fermentedcacao pod) and in period III sheep were given CF2 (fermented complete feed based cacao pod). Resultdemonstrated that pH value of sheep microbial liquid in treatment of CF0, CF1 and CF2 was in normalpH range and did not affect volatile fatty acids (VFA) and ammonia. In conclusion, supplementing up to 50% of feed with complete feed containing fermented or non-fermented cacao pod did not affect theprocess of rumen microbial fermentation.